Stereotypes of Batak Culture In the Movie Ngeri-Ngeri Sedap(Van Dijk Critical Discourse Analysis) - Rahim, M Rahim; Mustabir Halim (Jurnal Sastra Indonesia, 2024)
This article aims to present the results of a critical discourse analysis of the film Ngeri-Ngeri Sedap by director Bene Dion Rajagukguk so that people who have views or stereotypes of the Batak tribe can understand and enjoy the meaning contained in the movie and the cultural aspects within it. The type and approach applied in the research is descriptive-qualitative. The data is analyzed through Teun A. Van Dijk's critical discourse analysis model, which discusses the dimensions of text, social cognition, and social context. The results of this study show that there are stereotypes attached to Batak culture. At the macrostructure stage, it discusses several themes of the Batak culture ban. At the superstructure stage, it is found that the scheme in the film discusses the story that begins with the opening board, conflict, and the final result in the form of Mr. Domu's choice to be happy with his family even though his children violate the stereotypes of Batak culture. In the micro stage, parents use prohibitive words to their children. In the cognition stage, Bene Dion Rajagukguk has a goal to eliminate Batak cultural stereotypes that have been imposed in society. Then, in the social context stage, it provides an understanding of the need for a harmonious understanding between parents and children to create a happy continuity.